The 12 September 2016 Gyeongju earthquakes: 2. Temporary seismic network for monitoring aftershocks - Kim, Kwang-Hee; Kang, Tae-Seob; Rhie, Junkee; Kim, YoungHee; Park, Yongcheol; Kang, Su Young; Han, Minhui; Kim, Jeongmu; Park, Jechan; Kim, Minook; Kong, ChangHwan; Heo, Dabeen; et al. (Geosciences journal (Seoul, Korea), 2016)
The M L 5.8 earthquake in Gyeongju, southeastern Korea, on September 12, 2016 11:32:54 (UTC) was the largest earthquake on the Korean Peninsula since instrumental monitoring began in 1978. It was preceded by an M L 5.1 foreshock and is being followed by numerous aftershocks. Within an hour of the mainshock, the first temporary seismic station to monitor aftershocks was installed at about 1.5 km east of the announced epicenter. The current temporary seismic network consists of 27 stations equipped with broadband sensors covering an area of ∼38 × 32 km in the mainshock region. This is the first high-density aftershock monitoring array in the Korean Peninsula. Initial results, using data from both the regional seismic networks and the aftershock monitoring array, indicate that earthquakes during the first 10 days following the mainshock are related to the Yangsan Fault System. Establishment of an official rapid-response team to monitor aftershocks of major earthquakes is advised.